The immediate and delayed impact of a flipped learning-based program on university students’ learned helplessness - Mohammad H. Abood; Atef Abuhmaid (Institute of Advanced Engineering and Science, 2026)
Learned helplessness can significantly hinder academic achievement, necessitating effective pedagogical interventions. The current study investigated the impact of flipped learning as an innovative teaching approach on mitigating learned helplessness in higher education context. Forty undergraduate university students were involved in the study and they were randomly assigned to an experimental group (n=20) which received instruction through the flipped learning approach, or a control group (n=20) which received traditional instruction. Data collection was conducted using the learned helplessness scale. The results of the study revealed statistically significant differences between the experimental and control groups on the learned helplessness scale, indicating that the flipped learning group exhibited lower levels of learned helplessness. Students in the experimental group showed significant immediate reduction in their learned helplessness compared to students of the control group. Nevertheless, follow-up testing revealed that these gains significantly declined over time. This highlights a crucial distinction between the immediate and delayed effects of the pedagogical intervention. Practically, the findings suggest that while flipped learning is an effective tool for reducing learned helplessness, its benefits are transient without consistent reinforcement and systematic support rather than relying on one-time intervention.